RAM ratings reaffirms UniTapah's AA1 stable rating / News Team UiTM Perak - UiTM Perak, News Team (Universiti Teknologi MARA, Perak, 2020)
RAM Ratings has reaff irmed the AA1/Stable rating of UniTapah Sdn Bhd's (the Company) SukukMurabahah of up to RM600 mil (2014/2035). This is premised on the Company's strong and predictablecashflow debt-service coverage, supported by prompt receipts of monthly Availability Charges (ACs) fromUniversity Teknologi MARA (UiTM). The rating is further supported by UniTapah's good maintenance trackrecord and low counterparty risk.